AKTIVITAS KOMUNIKASI MASYARAKAT HINDU TAMIL DALAM UPACARA THAIPUSAM DI SINGAPURA - Mogot, Yuni (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2019)
This research aims to investigating Hindu Tamil communityâ€™s communication activities on Thaipusam ceremony at Singapore. A qualitative design with Ethnography of communication approach is used on this research. The data collection method is observation and participation on the research subjectâ€™s daily live, in-depth interview with 29 respondents who was decided purposively, literature study, also documents and data analysis that related to research objects. The results show that Communicative Situation on Thaipusam ceremony at Singapore take place until five kilometers, which started from Sri Sinivasa Perumal Temple at Serangoon Road, and ended at Sri Thendayuthapani Temple at Tank Road. Communicative Events on Thaipusam ceremony which followed by Hindu Tamil Community is the expression of gratitude and penance. The ceremony started at 02.00 P.M. local time, and ended at 04.00 P.M. on the next day. The Language that is used during the ceremonial ritual is the language from participants communityâ€™s origin, which is Tamil. Communicative Action which is done on the Thaipusam ceremony expressed on both verbal and non-verbal forms, such as utterances, pictures or photographs, praise gesture, facial expression, and clothes with orange domination. The glory of goodness from evil is symbolized through the use of â€œvelâ€ and â€œkavadiâ€ which are used during the ceremony.